O personal trainer e sua prática educativa - Brito, Fabio Lima De [UNIFESP] (2020)
INTRODUCTION: The Personal Trainer (PT) is a professional with a bachelor's degree in Physical Education who uses an individualized approach, assesses, motivates, educates and trains his students/clients for their health. In daily life, the PT must understand his actions regarding to the educational component of professional practice. Thus, the professional must be able to make the student/client autonomous regarding the physical activity and self-care. OBJECTIVE: To investigate the educational practice of the Personal Trainer (PT) in his role as a health promoter. Specifically: apprehend the PT's understandings on education and educational practice, evaluate the initial training for this practice, Identify the challenges encountered and map the suggestions presented to improve it. METHODOLOGY: A quantitative/qualitative, transversal, exploratory and descriptive approach was adopted based on two instruments: Likert-type attitudinal scale and in-depth interview. For the scale, we had a total of 203 participants. The interview was conducted with 15 participants who participated in the scale, in order to deepen the results obtained in it. Content analysis was used in the thematic modality and started from four thematic nuclei: Understanding about educational practice; The initial formation of the PT; The challenges found at work for educational practice; and suggestions for improving the practice. RESULTS AND DISCUSSION: The present study showed that there is an understanding of the PT regarding the educational practice implicit in his work activity with a view to promoting the health of his students / clients. In addition, their initial training takes place superficially and focused on biomechanical knowledge, with traditional teaching approaches based on know-how related specifically to physical exercise. The discussion about health promotion and about a dialogical and transformative educational practice with your student / client is insufficient. The student / client's resistance to exercise and the development of the educational component associated with orientation / prescription of physical exercise are the main challenges pointed out. The PTs suggest for improving the practice, greater awareness of their responsibility in building the autonomous knowledge of his student / client to maintain their self-care. FINAL COMMENTS: Finally, we highlight that there are few studies addressing this theme, so we suggest that there is more research focused on the educational practice of the PT.